Rekonstruksi Kepastian Hukum Terhadap Mahar Tanah dalam Pernikahan Masyarakat Bugis Makassar - Sudirman Sudirman (TASAMUH: Jurnal Studi Islam, 2021)
The focus of this research is the reconstruction legal certainty of land dowries in Makassar Bugis community marriages. The research method in this study uses descriptive qualitative. The findings in this study show that the existence of dowry land has been carried out by the Bugis Makassar people from the past to the present, so that it has become a habit. Although it is not practiced by all Bugis Makassar people. The status of giving dowries for land is often a problem due to the lack of legal certainty when the contract takes place. Authentic evidence such as certificates are still controlled by men, so that the handover is only symbolic. Moreover, the land used as a dowry is still under the control of the male family, and is still actively used by the male party, resulting in uncertainty of ownership. the land is for a wife on the transfer of rights due to dowry land. Until now, there has been no legal certainty that regulates the contracting of the dowry even though the initial evidence has been included in the marriage certificate. So it is very important for legal practitioners to formulate a legal basis for land dowries which are used as land dowries